Four wheels and one board: Studying the skateboard tribe and their loyalty towards skateboarding brands - Baumhammer, Paulo Miguel Pereira (2013)
Skateboarding is considered an extreme sport, but for its practitioners it represents much more. Skateboarders share a deep link because of the high level of passion and emotion revolving around skateboarding itself. In line with the previous, it is believed that we live in a postmodern-era suggesting that consumer’s value more symbolic and emotional aspects of products and services, rather than economic and functional ones. Furthermore, authors like Cova and Cova (2002) argue that consumers are willing to re-compose their social universe by connecting on an emotional basis with other consumers, forming consumer tribes. The First objective of this thesis is to understand if a consumer tribe can be identified within the Portuguese skateboarding panorama. The second one is to analyze how through a tribal marketing strategy skateboarding brands can achieve a true and emotional brand loyalty among the tribe. In order to accomplish these objectives an exploratory study was developed based on qualitative and ethnographic research including as main tools participant observation and in-depth interviews. Through the gathered data it was possible to verify that typical characteristics of consumer tribes were observed among skateboarders and sharing of common values such as non-competitive spirit and sense of freedom. Concerning the behavior and loyalty towards skateboard brands, the present findings support that these brands must establish an authentic and emotional relation with skateboarders by actively supporting and understanding the tribe and additionally take in account the main social influences in brand choice and loyalty.